Severity of Coronary Artery Involvement Correlates with Bone Turnover - M Jafar Mahmoodi; H Saghafi; F Karimi; H Behzadi; B Larijani (Tehran University of Medical Sciences, 2008)
Background: To evaluate bone turnover in coronary artery disease patients by using biochemical markers of bone formation and resorption. Methods: As a cross-sectional study, bone mineral density and serum osteocalcin and crosslaps were measured in 44 angiographically documented coronary artery disease patients and 30 people with normal angiography invited to Endocrinology and Metabolism Research Center. Results: Bone mineral density of femur was significantly lower in patient with coronary artery disease (P= 0.04). Prevalence of femur osteoporosis in patients with coronary artery disease was 43.2% whereas 14.8% of people with normal angiography had femur osteoporosis (P= 0.01, OR= 4.37; CI95%, 1.29-14, 77).Serum level of osteocalcin and crosslaps elevated significantly with increasing severity of coronary artery disease. A significantly positive correlation was found between coronary artery disease severity and serum level of osteocalcin (P= 0.008, r= 0.320). Crosslaps also showed similar correlation with number of diseased vessels (P= 0.02, r= 0.268). In multivariate analysis after adjustment of age, sex and BMI, severity of coronary artery disease was independently correlated with osteocalcin (P= 0.006) and crosslaps (P= 0.003). Conclusion: It seems that coronary artery disease and severity of atherosclerosis may be as a bone turnover predictor. Thus recommendation of Bone density and turnover evaluation to patients with a coronary event may be valuable for earlier diagnosis and prevention of osteoporosis and fracture.